Dimensi moral dalam Pendidikan Kewarganegaraan - AR, Muchson (Jurnal Civics: Media Kajian Kewarganegaraan, 2009)
In the past times, the moral issue is a core and main face of education. The talks about education, educators, or well-educated people refer ni"'ainfy to illustration of aspect of their morality and personality. Although the paradigm of education as a inheritance of values, especialfy moral values, are considered as an old-fashioned or conseruatiie, but , such education is very relevant for the solution to improve the morality of the nation. Subjects of Civic Education have distinctive vission, namely the formation of good citizens. Definition of ''good citizens" shows that the moral content is essential. However it is often based on interpretation of the ruler. As a consequence, these subfects are regarded as more political than academic and suf?jects with a weak saentificfoundation. As a part of formal curriatium, the moral dimension in Civic Education should be abso lutefy developed from the content or material standards. Beside, teachers with the aTttonomy thry had could inculcate moral values, whether unitersal or contextual or cultural or local. Thus, it is possible for teachers to develop iiformal curriculum or hidden curriculum, beside the formal curriculum